2013
DOI: 10.1159/000355575
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Metabolic Syndrome and Its Relationship with Physical Activity in Suburban Beijing, China

Abstract: Background: The present study aimed to estimate the up-to-date prevalence of metabolic syndrome and its relationship with physical activity among suburban adults in Beijing, China. Methods: A cross-sectional survey in a representative sample of 19,003 suburban adults aged 18-76 years was carried out in 2007-2008. Data was collected via questionnaires and blood pressure, anthropometric, and laboratory measurements. Results: Of the residents aged 18-76 years in suburban Beijing, 25.9% (27.3% in men and 25.1% in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 16 publications
2
5
0
Order By: Relevance
“…In this study, we found a high prevalence of MS of 20.1% among 26,836 participants in Yuhuan County, a coastal area located in developed East China, which was similar to previous studies ranging from 22.0 to 25.3%, and a higher prevalence for females was observed, which was consistent with previous studies [ 15 , 32 , 33 ]. Compared with the Northwest or other developing areas in China, MS was more prevalent in East China [ 34 , 35 ].…”
Section: Discussionsupporting
confidence: 92%
“…In this study, we found a high prevalence of MS of 20.1% among 26,836 participants in Yuhuan County, a coastal area located in developed East China, which was similar to previous studies ranging from 22.0 to 25.3%, and a higher prevalence for females was observed, which was consistent with previous studies [ 15 , 32 , 33 ]. Compared with the Northwest or other developing areas in China, MS was more prevalent in East China [ 34 , 35 ].…”
Section: Discussionsupporting
confidence: 92%
“…In this study, we found a high prevalence of MS of 20.1% among 26836 participants in Yuhuan County, a coastal area located in developed East China, which was similar to previous studies ranging from 22.0-25.3%, and a higher prevalence for females was observed, which was consistent with previous studies [14,25,26]. Compared with the Northwest or other developing areas in China, MS was more prevalent in East China [27,28].…”
Section: Discussionsupporting
confidence: 91%
“…Data from the China Health and Nutrition Surveys (CHNS) in 2009 showed that the prevalence of MetS was 18.2% and 10.5% using the definitions provided by the revised NCEP ATPIII and IDF, respectively [14]. WH Zhang and colleagues reported a prevalence of MetS of 25.3% in suburban Beijing during 2007–2008 [15]. Other studies of population-based studies estimated MetS prevalence among urban residents in China to be 26.04% to 32.5% in women and 17.91% to 35.1% in men using the IDF criteria [16, 17].…”
Section: Discussionmentioning
confidence: 99%